Trichome density and its UV-B protective potential are affected by shading and leaf position on the canopy (Environmental and Experimental Botany, 1997)
In Olea europaea trichome density and UV-B absorbing compounds of leaf hairs and the lamina proper of leaves located in south-facing, north-facing and the internal of the canopy were positively correlated to the UV-B midday instant irradiance measured in September at these three different positions of the canopy. The correlation between these three parameters and the receiving photosynthetically active radiation (PAR), however, was weaker. In Quercus ilex, trichome density and its UV-B absorbing capacity were considerably higher in the exposed, south-facing leaves, compared to the deeply shaded ones; the UV-B absorbing capacity of the de-haired lamina, however, was the same. In the broad- leaved, alpine rosette of Verbascum speciosum, one could distinguish two areas on the leaves, one exposed and one shaded by the superimposed lamina. Although trichome density and the UV-B absorbing compounds of the de-haired leaf were the same in the two areas, the UV-B absorbing capacity of hairs was considerably increased in the exposed region. In V. speciosum, exposure induced also qualitative changes in the UV-B absorbance profile, apparently due to the formation of new flavonoid compounds absorbing maximally at 345-350 nm. In all other cases, the differences were mainly quantitative. The results support the postulate of a function of leaf hairs as a UV-B radiation screen and suggest that trichome density and/or its UV-B absorbing capacity may depend on irradiance during leaf development.